A comparative analysis of the effects of misaligning different trifocal intraocular lenses - Yan, Weijia; Auffarth, Gerd U.; Khoramnia, Ramin; Łabuz, Grzegorz (Journal of Clinical Medicine, 2025)
Objectives: This laboratory study aims to assess the effects of misaligning different trifocal intraocular lenses (IOLs) under varying spectral and corneal spherical aberration (SA) conditions. Methods: With an IOL metrology device under monochromatic and polychromatic conditions, the following models were studied: AT ELANA 841P, AT LISA Tri 839MP, FineVision HP POD F, Acrysof IQ PanOptix, and Tecnis Synergy ZFR00V. The SA was simulated using an aberration-free and average-SA cornea. The modulation transfer function (MTF) was measured at different pupil sizes for the on- and off-axis lens positions. Results: The IOLs exhibited varying responses to decentration up to 1 mm, showing the lowest impact in polychromatic light. The least affected was AT ELANA, with an MTF loss of 15.7% to 28.4% at 50 lp/mm across the studied conditions. It was followed by PanOptix and FineVision, with the MTF loss ranging from 19.1% to 36.0% and from 21.2% to 46.6%. AT LISA showed a more substantial reduction, i.e., 41.2% to 64.8%, but it was still lower than that of Synergy (51.1% to 78.8%). When decentration was induced at a 4.5 mm distance, its effect was more evident in conditions that were closer to each IOL’s SA correction. A tilt of 5° had a lesser impact than 1 mm decentration, with the effect being more severe at 4.5 mm. Conclusions: The off-axis position affects the optical quality of trifocal IOLs. Low- rather than high-SA-correcting trifocals perform better under misalignment. In polychromatic light, the impact of misalignment is less evident, suggesting a potential mitigating effect of chromatic aberration.
Gesehen am 18.06.2025